World music [ a global journey - Miller, Terry E.; Shahriari, Andrew (New York : Routledge, 2009)
Introduces students to the diversity of musical expression around the world. This title takes the reader across the globe to experience cultural traditions that challenge the ear, the mind, and the spirit. It presents a systematic study of varied traditions in a non-technical language accessible to various enthusiasts of world music and culture
1. Before the trip begins : fundamental issues -- 2. Aural analysis : listening to the world's music -- 3. Cultural considerations : beyond the sounds themselves -- 4. Oceania : voices of land and sea -- 5. South Asia : music with a spiritual dimension -- 6. Southeast Asia : a land of bamboo and bronze --7. East Asia : ancient echoes in the modern world -- 8. The Middle East : music in the cradle of great religions -- 9. Sub-Saharan Africa : the rhythms of community -- 10. Europe : harmony and hierarchy -- 11. The Caribbean : musical energy of island peoples -- 12. Central and South America : New World recipes -- 13. North America : diverse peoples, diverse musics --Discovering yourself through music
Description based on print version record
Includes bibliographical references (p 534-542) and index
Keywords: Ethnomusicology